Commercialization of Patents and External Financing during the R&D-Phase - Roger Svensson (The Research Institute of Industrial Economics (IUI), 2004)
Using a unique database on individual Swedish patents, a survival model estimates how different factors influence the time it takes until commercialization starts. To the best of my knowledge, such an analysis has not been undertaken before. For external financing of patent projects and small technology-based firms, Sweden has during long time relied on government support rather than private venture capital firms. The empirical results show that the larger share of the patent-owners costs during the R&D-phase that are covered by government financial support, the longer time it takes until the patents are commercialized. It seems like the government financing creates a pool of patents with bad perspectives of commercialization. The reasons to the bad performance are: 1) the design of the government loans, where the patent owner can escape from paying back the loan if the project failures; and 2) the competence and incentives of the government institutions, which are not profit maximizing. A policy implication is therefore that the government should either change the conditions of the loans or, preferably, stop acting as a venture capital firm. The government should instead facilitate private solutions and the growth of private venture capital firms.
Keywords: G30; M13; O31; O38; 330; Patents; R&D; Commercialization; External Financing; Survival Models; Patent; Subvention; Forschungsfinanzierung; Schweden; Kommerzialisierung